Euphemism in Article Online on Konsultasi Syariah - Rindi - Puspita; Sri Minda Murni; Sumarsih - - (Universitas Negeri Medan, 2020)
The objective of this study is to explain the reason of using euphemism in religious language especially in article on Konsultasi Syariah. The research methodology used in the research is qualitative research design. The data were analyzed by using interactive model of qualitative data management and analysis namely data collection, data condensation, data display and verification and conclusion. The findings of this study revealed that the reasons of writer used euphemism especially in religious language tot only to make fear but also avoid taboo words, to show respect and to avoid uncomfortable feelings. The conclusion is euphemism that used on Konsutasi Syariah are in Arabic language and the most dominant used for taboo words Keywords: Euphemism, Religious Language, Article, Online